Digital simulations for improving education learning through artificial teaching environments - Gibson, David, Ed. D.; Baek, Youngkyun (Information Science Reference, 2009)
"This book is for anyone who is looking into games and simulations with an eye to their potential for improving teaching and learning"--Provided by publisher.